PEMBENTUKAN KREATIVITAS DAN KECERDASAN KINESTETIK ANAK USIA DINI MELALUI KEGIATAN SENI TARI DI TK KELURAHAN SOKANEGARA KECAMATAN PURWOKERTO TIMUR - Nurazizah; Wahyu Purwasih (QURROTI, 2023)
The aim of the study was to determine the formation of children's creativity and kinesthetic intelligence through dance activities in Kindergarten in Sokanegara Village, East Purwokerto District, Banyumas Regency. The research method used is phenomenological descriptive qualitative. The subjects of this study included teachers, principals and students of TK Kelurahan Sokanegara who consistently participated in dance activities, totaling 15 children. Based on the results of the research, it shows that the formation of children's creativity and kinesthetic intelligence through dance activities shapes children's creativity towards art, the child's body becomes flexible, the child can move skillfully according to the rhythm of the music that accompanies it, the coordination of thoughts and movements can be carried out well, and increase the power attract children to be able to move freely, as well as mentally train children when they dare to appear in front of many people. The formation of children's creativity and kinesthetic intelligence through dance activities includes planning which includes preparation for dance activities. The implementation of dance with several steps is carried out, namely arranging rows according to the child's height, providing material and examples of dance movements, selecting children who look creative and able to move in dancing and consistently follow the exercises, as well as evaluating art activities that have been carried out between exercises and after finished participating in certain events or appearances.